A hypothesis on the role of the human immune system in covid-19. (October 2020) - Khashkhosha, Hind Khairi; Elhadi, Muhammed
Abstract: The COVID-19 pandemic has not spared any continent. The disease has affected more than 7, 500, 000 individuals globally and killed approximately 450, 000 individuals. The disease is caused by a very small virus named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is an enveloped single-stranded RNA virus with a spike-like structure on its envelope that can interact with the angiotensin-converting enzyme 2 (ACE2) receptor after cleavage. ACE2 receptors are present in the human lungs and other organs. SARS-CoV-2 is a new virus that belongs to the subgenus Sarbecovirus; viruses in this subgenus have spread widely in the previous years and caused outbreaks of severe acute respiratory syndromes.